South African indigenous chickens' genetic diversity, and the adoption of ecological niche modelling and landscape genomics as strategic conservation techniques - Reneilwe Rose Mogano; Takalani Judas Mpofu; Bohani Mtileni; Khanyisile Hadebe (Poultry Science)
Selection pressures found in the prevailing production environments have shaped the genetic structure of indigenous chickens we see today. Indigenous chickens, raised in villages, provide essential genetic resources and income for poverty alleviation by providing affordable protein. However, they are threatened by predators, emerging diseases, and market demand for ideal breeds and fast production which causes loss of their valuable traits. The lack of knowledge about genetic diversity and genetic mechanisms underlying adaptive variants may compromise the goal of conserving indigenous chicken breeds. The main insights of the study are that indigenous chickens are highly diversified, and environmental factors play a key role in enabling chicken adaptation and distribution. Genomic and spatial technologies have made it possible to explore the genetic structure and fully comprehend the mechanism underlying the local adaptation of indigenous chickens. These technologies can aid in creating programs that enhance productivity and promote climate-resilient breeds. This review explores the impact of natural selection on indigenous chicken, genetic diversity, population size, and the advancement of technologies in understanding local adaptation drivers. In conclusion, this review highlights the importance of studying the habitats and how this will guide in conserving local breeds in their intended production environment.